Mechanisms, Cofactors, and Augmenting Factors Involved in Anaphylaxis - Muñoz-Cano, Rosa; Pascal, Mariona; Araujo, Giovanna; Goikoetxea, M. J.; Valero, Antonio L.; Picado, Cesar; Bartra, Joan (Frontiers in Immunology, 2017)
Anaphylaxis is an acute and life-threatening systemic reaction. Many triggers have been described including food, drug and hymenoptera allergens which are the most frequently involved. The mechanisms described in anaphylactic reactions are complex and implicate a diversity of pathways. Some of these mechanisms may be key to the development of the anaphylactic reaction, whilst others may only modify its severity. Although specific IgE, mast cells and basophils are considered the principal players in anaphylaxis, alternative mechanisms have been proposed in non-IgE anaphylactic reactions. Neutrophils, macrophages as well as basophils, have been involved, as have IgG-dependent, complement, and contact system activation. A range of cationic substances can induce antibody-independent mast cells activation through MRGPRX2 receptor. Cofactors and augmenting factors may explain why in some patients food allergen exposure can cause anaphylaxis, while in other clinical scenario it can be tolerated or elicits a mild reaction. With the influence of these factors, food allergic reactions may be induced at lower doses of allergen and/or become more severe. Exercise, alcohol, estrogens and some drugs such as Nonsteroidal anti-inflammatory drugs, angiotensin-converting enzyme inhibitors, β-blockers and lipid-lowering drugs are the main factors described, though their mechanisms and signaling pathways are poorly understood.